Identifying Leafhopper Targets for Controlling Aster Yellows in Carrots and Celery - Patrick T. Stillson (Insects, 2020)
Aster yellows phytoplasma (Candidatus Phytoplasma asteris) is a multi-host plant pathogen and is transmitted by at least 24 leafhopper species. Pathogen management is complex and requires a thorough understanding of vector dynamics. In the American Midwest, aster yellows is of great concern for vegetable farmers who focus on controlling one vector, Macrosteles quadrilineatus—the aster leafhopper. However, vegetable-associated leafhopper communities can be diverse. To investigate whether additional species are important aster yellows vectors, we surveyed leafhopper communities at commercial celery and carrot farms in Michigan from 2018 to 2019 and conducted real-time PCR to determine infection status. Leafhoppers were collected within crop fields and field edges and identified with DNA barcoding. Overall, we collected 5049 leafhoppers, with the most abundant species being M. quadrilineatus (57%) and Empoasca fabae—the potato leafhopper (23%). Our results revealed the most abundant aster yellows vector in Michigan in both crops is M. quadrilineatus, but we also found that E. fabae may be a potential vector for this pathogen. While several taxa reside in and near these crops, we did not find strong evidence that they contribute to phytoplasma infection. These findings indicate that M. quadrilineatus should be the primary target for controlling this pathogen.